2013
DOI: 10.1021/pr3010293
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Striped Bass (Morone saxatilis) Ovary Proteome Reveal a Complex Network of the Translasome

Abstract: We evaluated changes in the striped bass (Morone saxatilis) ovary proteome during the annual reproductive cycle using label-free quantitative mass spectrometry and a novel machine learning analysis based on K-means clustering and support vector machines. Modulated modularity clustering was used to group co-variable proteins into expression modules and Gene Ontology (GO) biological process and KEGG pathway enrichment analyses were conducted for proteins within those modules. We discovered that components of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 56 publications
0
45
0
Order By: Relevance
“…NanoLC-MS/MS data for all proteins are reported in Reading et al ( 24 ). The Lrp13 in the ovary during LVG and PVG was elevated compared with ESG ( P < 0.0402) ( Fig.…”
Section: Quantitative Tandem Mass Spectrometrymentioning
confidence: 76%
See 3 more Smart Citations
“…NanoLC-MS/MS data for all proteins are reported in Reading et al ( 24 ). The Lrp13 in the ovary during LVG and PVG was elevated compared with ESG ( P < 0.0402) ( Fig.…”
Section: Quantitative Tandem Mass Spectrometrymentioning
confidence: 76%
“…Aliquots of solubilized ovary membrane proteins, affi nity purifi ed Vtgrs, and purifi ed VtgAa/b were processed for LC-ESI-MS/MS using an LTQ linear ion trap mass spectrometer (Thermo, San Jose, CA) at the NCSU Genomic Sciences Laboratory (Raleigh, NC). Samples were analyzed in quadruplicate and ion fragmentation spectra were queried by MASCOT (Matrix Science, Boston, MA) against white perch VtgAa, VtgAb, VtgC ( 16 ), white perch Lr8 Ϫ ( 18 ), and the translated striped bass ovary transcriptome ( 24,25 ).…”
Section: Protein-affi Nity Chromatographymentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a transcriptional analysis of fathead minnow ovaries after exposure to a model androgen and antiandrogen identified transcriptional regulators as potential early molecular switches to control phenotypic changes in ovary in response to androgen or antiandrogen exposure (Garcia-Reyero et al, 2009c). Reading et al (2013) used proteomics to examine the ovary in striped bass and found that the proteasome-ribosome supercomplex known as translasome may play an important role of during the ovarian cycle. Flatfish are also of great interest in aquaculture and an oligo-based microarray for the senegalese sole based on multi-tissue library sequencing was developed (Cerdà et al, 2008).…”
Section: Use Of Omics Technologies In Endocrine Researchmentioning
confidence: 99%